Cinnamon - Gaiman, Neil (Harper, an Imprint of HarperCollinsPublishers, 2017)
Cinnamon was a princess, a long time ago, in a small hot country, where everything was very old. Cinnamon did not talk. Mango trees, a parrot, and a beautiful room in the palace do nothing to help the teachers who try to make her to speak. Can a man-eating tiger do so, and exactly who will end up in the belly of the beast?